mTOR and autophagy pathways are dysregulated in murine and human models of Schaaf-Yang syndrome - Crutcher, Emeline; Pal, Rituraj; Naini, Fatemeh; Zhang, Ping; Laugsch, Magdalena; Kim, Jean; Bajic, Aleksandar; Schaaf, Christian P. (Scientific reports, 2019)
MAGEL2 is a maternally imprinted, paternally expressed gene, located in the Prader-Willi region of human chromosome 15. Pathogenic variants in the paternal copy of MAGEL2 cause Schaaf-Yang syndrome (SHFYNG), a neurodevelopmental disorder related to Prader-Willi syndrome (PWS). Patients with SHFYNG, like PWS, manifest neonatal hypotonia, feeding difficulties, hypogonadism, intellectual disability and sleep apnea. However, individuals with SHFYNG have joint contractures, greater cognitive impairment, and higher prevalence of autism than seen in PWS. Additionally, SHFYNG is associated with a lower prevalence of hyperphagia and obesity than PWS. Previous studies have shown that truncating variants in MAGEL2 lead to SHFYNG. However, the molecular pathways involved in manifestation of the SHFYNG disease phenotype are still unknown. Here we show that a Magel2 null mouse model and fibroblast cell lines from individuals with SHFYNG exhibit increased expression of mammalian target of rapamycin (mTOR) and decreased autophagy. Additionally, we show that SHFYNG induced pluripotent stem cell (iPSC)-derived neurons exhibit impaired dendrite formation. Alterations in SHFYNG patient fibroblast lines and iPSC-derived neurons are rescued by treatment with the mTOR inhibitor rapamycin. Collectively, our findings identify mTOR as a potential target for the development of pharmacological treatments for SHFYNG.